Comparative transcriptomics provides novel insights into the mechanisms of selenium accumulation and transportation in tea cultivars (Camellia sinensis (L.) O. Kuntze) - Zheng, Qinghua; Guo, Lina; Huang, Jianyan; Hao, Xinyuan; Li, Xiaoman; Li, Nana; Wang, Yueqi; Zhang, Kexin; Wang, Xinchao; Wang, Lu; Zeng, Jianming (Frontiers in Plant Science, 2023)
Tea plants (Camellia sinensis) show discrepancies in selenium accumulation and transportation, the molecular mechanisms of which are not well understood. Hence, we aimed to conduct a systematic investigation of selenium accumulation and transportation mechanisms in different tea cultivars via transcriptomic analysis. Na2SeO3 and Na2SeO4 treatment improved selenium contents in the roots and leaves of three tea cultivars. The high selenium-enrichment ability (HSe) tea cultivars accumulated higher selenium contents in the leaves than did the low selenium-enrichment ability (LSe) tea cultivars. Transcriptomic analysis revealed that differentially expressed genes (DEGs) under Na2SeO3 and Na2SeO4 treatments were enriched in flavonoid biosynthesis in leaves. DEGs under Na2SeO3 treatment were enriched in glutathione metabolism in the HSe tea cultivar roots compared to those of the LSe tea cultivar. More transporters and transcription factors involved in improving selenium accumulation and transportation were identified in the HSe tea cultivars under Na2SeO3 treatment than Na2SeO4 treatment. In the HSe tea cultivar roots, the expression of sulfate transporter 1;2 (SULTR1;2) and SULTR3;4 increased in response to Na2SeO4 exposure. In contrast, ATP-binding cassette transporter genes (ABCs), glutathione S-transferase genes (GSTs), phosphate transporter 1;3 (PHT1;3), nitrate transporter 1 (NRT1) and 34 transcription factors were up-regulated in the presence of Na2SeO3. In the HSe tea cultivar leaves, ATP-binding cassette subfamily B member 11 (ABCB11) and 14 transcription factors were up-regulated under Na2SeO3 treatment. Among them, WRKY75 was explored as a potential transcription factor that positively regulated the accumulation of Na2SeO3 in the roots of HSe tea cultivars. This study preliminary clarified the mechanism of selenium accumulation and transportation in tea cultivars, and the findings have important theoretical significance for the breeding and cultivation of selenium-enriched tea cultivars.